Improving Emergency Department radiology transportation time: a successful implementation of lean methodology - Eveline A. Hitti; Ghada R. El-Eid; Hani Tamim; Rana Saleh; Miriam Saliba; Lena Naffaa (BMC, 2017)
Abstract Background Emergency Department overcrowding has become a global problem and a growing safety and quality concern. Radiology and laboratory turnaround time, ED boarding and increased ED visits are some of the factors that contribute to ED overcrowding. Lean methods have been used in the ED to address multiple flow challenges from improving door-to-doctor time to reducing length of stay. The objective of this study is to determine the effectiveness of using Lean management methods on improving Emergency Department transportation times for plain radiography. Methods We performed a before and after study at an academic urban Emergency Department with 49,000 annual visits after implementing a Lean driven intervention. The primary outcome was mean radiology transportation turnaround time (TAT). Secondary outcomes included overall study turnaround time from order processing to preliminary report time as well as ED length of stay. All ED patients undergoing plain radiography 6 months pre-intervention were compared to all ED patients undergoing plain radiography 6 months post-intervention after a 1 month washout period. Results Post intervention there was a statistically significant decrease in the mean transportation TAT (mean ± SD: 9.87 min ± 15.05 versus 22.89 min ± 22.05, respectively, p-value <0.0001). In addition, it was found that 71.6% of patients in the post-intervention had transportation TAT ≤ 10 min, as compared to 32.3% in the pre-intervention period, p-value <0.0001, with narrower interquartile ranges in the post-intervention period. Similarly, the "study processing to preliminary report time" and the length of stay were lower in the post-intervention as compared to the pre-intervention, (52.50 min ± 35.43 versus 54.04 min ± 34.72, p-value = 0.02 and 3.65 h ± 5.17 versus 4.57 h ± 10.43, p < 0.0001, respectively), in spite of an increase in the time it took to elease a preliminary report in the post-intervention period. Conclusion Using Lean change management techniques can be effective in reducing transportation time to plain radiography in the Emergency Department as well as improving process reliability.